Overexpression of KCNJ2 in induced pluripotent stem cell-derived cardiomyocytes for the assessment of QT-prolonging drugs - Min Li; Yasunari Kanda; Takashi Ashihara; Tetsuo Sasano; Yuji Nakai; Masami Kodama; Erina Hayashi; Yuko Sekino; Tetsushi Furukawa; Junko Kurokawa (Elsevier, 2017)
Human induced pluripotent stem cell (hiPSC)-derived cardiomyocytes hold great potentials to predict pro-arrhythmic risks in preclinical cardiac safety screening, although the hiPSC cardiomyocytes exhibit rather immature functional and structural characteristics, including spontaneous activity. Our physiological characterization and mathematical simulation showed that low expression of the inward-rectifier potassium (IK1) channel is a determinant of spontaneous activity. To understand impact of the low IK1 expression on the pharmacological properties, we tested if transduction of hiPSC-derived cardiomyocytes with KCNJ2, which encodes the IK1 channel, alters pharmacological response to cardiac repolarization processes. The transduction of KCNJ2 resulted in quiescent hiPSC-derived cardiomyocytes, which need pacing to elicit action potentials. Significant prolongation of paced action potential duration in KCNJ2-transduced hiPSC-derived cardiomyocytes was stably measured at 0.1 μM E-4031, although the same concentration of E-4031 ablated firing of non-treated hiPSC-derived cardiomyocytes. These results in single cells were confirmed by mathematical simulations. Using the hiPSC-derived cardiac sheets with KCNJ2-transduction, we also investigated effects of a range of drugs on field potential duration recorded at 1 Hz. The KCNJ2 overexpression in hiPSC-derived cardiomyocytes may contribute to evaluate a part of QT-prolonging drugs at toxicological concentrations with high accuracy.